Pengaruh Pembelajaran Contextual Teaching And Learning Terhadap Hasil Belajar Siswa Kelas IV Pada Mata Pelajaran Akidah Akhlak : Pembelajaran CTL - Siti Nurhayati; Nana Mulyana; Supriyatin (STIT Sirojul Falah Bogor, 2023)
ABSTRACK Contextual Teaching and Learning is a learning process that links the material being studied with students' real life or student experiences. With the development of science, students' ways of thinking also develop which need to be directed by a learning process that is able to provide students with an understanding of the material being studied. The understanding that will be obtained based on the experience or real life of students will be easier to remember. This study aims to determine the effect of Contextual Teaching and Learning of fourth grade students’ learning outcomes on the subject of moral aqidah at SDIT Baitul Hilmi Cibinong. The method used in this study is a quantitative method. This method is used to determine the extent of the influence of contextual teaching and learning on the learning outcomes of fourth grade students on the subjects of aqidah morality at SDIT Baitul Hilmi Cibinong. The research instrument used to obtain data was by using a questionnaire (questionnaire) in the form of a checklist. Data processing is carried out by correlation analysis of Product Moment. The variables studied in this study are the influence of contextual teaching and learning (X) on learning outcomes of morals (Y) Based on the product moment analysis, the value of